Strategi Pengembangan Usaha Biliar Melalui Pendekatan Analisis SWOT di Kota Uneng, Kabupaten Sikka - Emilianus Eo Kutu Goo; Maria Fransiska Angelina; Maria Meliani; Maria Paulina Novitasari; Oktavia Jaslina Rini; Maria Oktavia Alexandria (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to formulate development strategies for a billiard business in Kota Uneng, Sikka Regency, using the SWOT analysis approach. The activity was carried out through field observations, interviews with the business owner, SWOT training sessions, and guided preparation of the strategic matrix. The analysis indicates several strengths, including a strategic location, adequate facilities, and affordable service prices. However, weaknesses were also identified, such as limited capital, insufficient promotional activities, and suboptimal operational management. Opportunities arise from the growing interest in recreational activities and the potential for collaboration with local community groups. Meanwhile, threats include competition from similar businesses and shifts in entertainment preferences. Based on these findings, SO, WO, ST, and WT strategies were formulated to be implemented gradually to enhance competitiveness and ensure business sustainability. These strategies provide a practical guide for improving service quality and strengthening the market position of the billiard enterprise.